A behavioral analysis of two spaces in Kansas State University's Hale Library based on psychologist Roger Barker's behavior setting theory - Manandhar, Sachit (Kansas State University, 2014)
This thesis uses behavioral mapping to analyze two contrasting spaces in Kansas State University’s Hale Library. One of the spaces is meant for computer use; and the other for general library use, including study-group work. The conceptual approach chosen to describe and analyze these two library spaces is the behavior-setting theory developed by psychologist Roger Barker, who defines behavior settings as independent units of space, with temporal and spatial boundaries, that have “great coercive power over the behaviors that occur within them” (Barker, 1968, p. 17). The behavioral observations for the two Hale Library spaces were analyzed and compared with findings from other studies of library usage and behaviors. In the first chapter of the thesis, I introduce my study topic and discuss recent developments in libraries. In the second chapter, I provide a broad overview of library history and library use. I also overview behavior-setting theory and present examples of research on behavior settings and libraries. In the third chapter, I discuss research methods for this thesis, starting with how library spaces can be described as behavior settings. I then discuss specific methodological procedures involved in the behavioral study of activities in the two library spaces. In the fourth chapter, I discuss the two spaces studied in Hale Library, first, describing their physical features and then discussing their behavior-setting attributes. In the fifth chapter, I present my behavioral observations and compare and contrast the two Hale Library spaces in terms of user behaviors and as behavior settings. In the sixth and final chapter of this thesis, I compare my research results with other library research and offer my speculative ideas on the future of the academic library. The overarching theme of this thesis is evaluating how recent digital technologies have affected libraries, and how traditional library spaces and spaces designated for digital technology can be integrated in future libraries.
Keywords: Library usage; Hale Library; Library and technology; Behavior settings; Future of academic libraries; User behaviors in libraries; Architecture (0729); Behavioral Sciences (0602); Library Science (0399)